The Study of Practice in the Vehicles of Men and Gods and the Bodhisattva Vehicle: Perspectives from Master Taixu to Master Hsing Yun - Chienhuang Chen (Religions, 2025)
This paper explores the perspectives of Master Taixu (太虛, 1890–1947) and Master Hsing Yun (星雲, 1927–2023) on the practice of the Buddhist Five Vehicles (五乘), particularly focusing on the relationship between the Vehicles of Men and Gods (人天乘) and the Bodhisattva Vehicle (菩薩乘). Master Taixu advocated “Buddhism for Human Life” (人生佛教), emphasizing the improvement of real life as the foundation for Buddhist practice in daily life. He proposed the principle of “following the practice and fruition of the Human Vehicle to cultivate the Mahāyāna path” (依人乘行果，趣修大乘行), suggesting a gradual progression from the human vehicle to the Mahāyāna Bodhisattva path. He introduced the concept of “The perfection of human character leads to Buddhahood” (人圓佛即成) and “Present Bodhisattva Practice” (今菩薩行), highlighting the importance of adapting Buddhist practice to contemporary society and actively engaging in social service. Master Hsing Yun’s advocacy of “Humanistic Buddhism” (人間佛教) emphasizes the diversity of practice, asserting that any action aligned with Buddhist teachings, beneficial to human well-being, and conducive to the welfare of all beings constitutes a form of practice, thereby expanding its definition. He elaborated on the Five Vehicles, viewing the Vehicle of Men and Gods as a preliminary stage, advocating a gradual progression towards the Bodhisattva Vehicle, ultimately culminating in Buddhahood. He proposed the principle of “undertaking worldly affairs with an otherworldly mindset” (以出世的思想，做入世的事業), highlighting the importance of practicing the Bodhisattva path in everyday life. With “Buddha Light Pure Land” (佛光淨土) as the ultimate goal, he sought to integrate the essence of various Pure Lands traditions to achieve earthly peace and purification. Both masters highlight the importance of practicing Humanistic Buddhism, advocating for the application of the Bodhisattva practice in daily life, guiding all beings with compassion and wisdom, and actively engaging in society to address real-world issues, ultimately realizing a Humanistic Pure Land. However, their perspectives also differ: Master Taixu focused more on the theoretical construction and an exposition on the order of practice, whereas Master Hsing Yun placed greater emphasis on the diversity and flexibility of practice and the integration of Buddhist teachings into modern life.